Land Policy Strategy in Peatlands of Pandan Sejahtera Village, Geragai District, East Tanjung Jabung Regency - Dwi Nila Wahyuningsih; Ernan Rustiadi; Didit Okta Pribadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The condition of land ownership, possession, and use in Pandan Sejahtera Village is predominantly characterized by unregistered land under mixed garden use. Among registered lands, corporate ownership dominates with a Right to Cultivate (Hak Guna Usaha) of 1,009.85 hectares, primarily for oil palm plantations, compared to individual ownership (Hak Milik). The regulatory framework of the Indicative Moratorium Map on Primary Forests and Peatlands (PIPPIB) serves as the main reference for reviewing land policy in the peatlands of Pandan Sejahtera. The PIPPIB boundary aligns with the provincial forest zone boundary in Jambi. Based on Ribot and Peluso’s (2003) Access Theory, structural authority mechanisms influence the legality and land use rights of peatland areas recognized under the law. Policy recommendations highlight the S1,O2 strategy as a priority, emphasizing the utilization of existing regulations and technical support from institutions for peatland restoration as a key opportunity for effective land policy implementation.